555. Characteristics of HIV+ Patients Prescribed Raltegravir QD in the United States. (26th November 2018) - Lackey, Philip; Schulman, Kathy; Fusco, Jennifer; Arduino, Jean Marie; Prajapati, Girish; Fusco, Gregory
Abstract: Background: Raltegravir (RAL) 400 mg twice-daily (RAL BID) has been an integral part of antiretroviral therapy (ART) in both ART naïve and experienced HIV-1 infected patients for the last decade. In 2017, RAL 1, 200 mg (2 × 600 mg), a once-daily formulation (RAL QD) was approved. The objective of this study was to characterize the early utilization of RAL QD in the United States. Methods: This is an ongoing cohort study of HIV-1 infected adults with ≥1 prescription for RAL QD in the OPERA ® Observational Database, the product of a collaboration of HIV caregivers in 84 clinics across 17 states following over 80, 000 people living with HIV through their prospectively collected electronic medical records. Baseline demographic, clinical and laboratory characteristics of patients who initiated RAL QD between July 1 and December 31, 2017 (study window) were analyzed using descriptive statistics. Results: A total of 175 patients were prescribed RAL QD during the study window; 57.1% of whom were ≥50 years of age, 80.6% male, 41.1% African American, and 20.0% Hispanic (Figure 1). RAL QD was most often given with emtricitabine/tenofovir (TDF or TAF): 56.0%, abacavir/lamivudine: 8.0%, and darunavir/cobicistat: 4.6%. Twelve patients (7%) were ART naïve, 45 (26%) switched from non-RAL-based regimens, and 118 patients (67%) were previously on RAL BID, most of whom (86%) had no other regimen changes other than switching to RAL QD. A majority (80%) of patients initiated RAL QD with a viral load <200 copies/mL; 68.6% were suppressed to <50 copies at baseline. Similarly, 77.1% had CD4 counts >350 cells/mm 3 ; 64.0% >500 cells/mm 3 . Overall, a third of patients had a history of an AIDS-defining illness. Eighty-one percent of patients had at least one of the comorbidities depicted in Figure 2; 45.7% with hypertension, 42.9% hyperlipidemia, 26.7% anxiety disorders, 26.3% anemia and 19.4% with diabetes. The median number of prescriptions for concomitant medications prescribed with RAL QD regimens was 5 (IQR: 4–8). Conclusion: Early initiators of RAL QD are primarily treatment-experienced individuals, older than 50 years of age with virologic and immunologic control, significant comorbid conditions and the burden of medications that treat those conditions. Disclosures: J. Fusco, Epividian, Inc.: Employee, Salary. Merck & Co.: Merck contracted research with my employer, Epividian, Inc., Employer received funding for research. J. M. Arduino, Merck Sharp & Dohme Corp: Employee and Shareholder, Salary. G. Prajapati, Merck & Co., Inc.: Employee and Shareholder, Salary. G. Fusco, Epividian, Inc.: Employee, Salary. Merck & Co.: Merck research contract with Epividian, employer received funding to perform analysis.